High-resolution multi-band imaging for validation and characterization of small kepler planets - Everett, Mark E.; Barclay, Thomas; Ciardi, David R.; Horch, Elliott P.; Howell, Steve B.; Crepp, Justin R.; Silva, David R. (The Astronomical Journal, 2015)
High-resolution ground-based optical speckle and near-infrared adaptive optics images are taken to search for stars in close angular proximity to host stars of candidate planets identi fied by the NASA Kepler Mission. Neighboring stars are a potential source of false positive signals. These stars also blend into Kepler light curves, affecting estimated planet properties, and are important for an understanding of planets in multiple star systems. Deep images with high angular resolution help to validate candidate planets by excluding potential background eclipsing binaries as the source of the transit signals. A study of 18 Kepler Object of Interest stars hosting a total of 28 candidate and validated planets is presented. Validation levels are determined for 18 planets against the likelihood of a false positive from a background eclipsing binary. Most of these are validated at the 99% level or higher, including five newly validated planets in two systems: Kepler-430 and Kepler-431. The stellar properties of the candidate host stars are determined by supplementing existing literature values with new spectroscopic characterizations. Close neighbors of seven of these stars are examined using multi-wavelength photometry to determine their nature and influence on the candidate planet properties. Most of the close neighbors appear to be gravitationally bound secondaries, while a few are best explained as closely co-aligned field stars. Revised planet properties are derived for each candidate and validated planet, including cases where the close neighbors are the potential host stars. © 2015. The American Astronomical Society. All rights reserved.
46 citations (Crossref) [2023-10-31] Citation Key Alias: pop00061 tex.type: [object Object]
Keywords: Binaries: visual; Planetary systems; Planets and satellites: detection; Planets and satellites: fundamental parameters; Surveys; Techniques: high angular resolution; dept.phy; peer-reviewed

A comparison of spectroscopic versus imaging techniques for detecting close companions to kepler objects of interest - Teske, Johanna K; Everett, Mark E; Hirsch, Lea A; Furlan, Elise; Horch, Elliott P; Horch, Elliott P; Howell, Steve B; Ciardi, David R; Gonzales, Erica J; Crepp, Justin R (The Astronomical Journal, 2015)
Kepler planet candidates require both spectroscopic and imaging follow-up observations to rule out false positives and detect blended stars. Traditionally, spectroscopy and high-resolution imaging have probed different host star companion parameter spaces, the former detecting tight binaries and the latter detecting wider bound companions as well as chance background stars. In this paper, we examine a sample of 11 Kepler host stars with companions detected by two techniques - near-infrared adaptive optics and/or optical speckle interferometry imaging, and a new spectroscopic deblending method. We compare the companion effective temperatures (Teff) and flux ratios (FB/FA, where A is the primary and B is the companion) derived from each technique and find no cases where both companion parameters agree within 1σ errors. In 3/11 cases the companion Teff values agree within 1σ errors, and in 2/11 cases the companion FB/FA values agree within 1σ errors. Examining each Kepler system individually considering multiple avenues (isochrone mapping, contrast curves, probability of being bound), we suggest two cases for which the techniques most likely agree in their companion detections (detect the same companion star). Overall, our results support the advantage that the spectroscopic deblending technique has for finding very close-in companions (θ ≲ 0.″02-0.″05) that are not easily detectable with imaging. However, we also specifically show how high-contrast AO and speckle imaging observations detect companions at larger separations (θ ≥ 0.″02-0.″05) that are missed by the spectroscopic technique, provide additional information for characterizing the companion and its potential contamination (e.g., position angle, separation, magnitude differences), and cover a wider range of primary star effective temperatures. The investigation presented here illustrates the utility of combining the two techniques to reveal higher-order multiples in known planet-hosting systems. © 2015. The American Astronomical Society. All rights reserved.
14 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/163-960-215-288-558 tex.type: [object Object]
Keywords: binaries: general; dept.phy; peer-reviewed; planetary systems; techniques: high angular resolution; techniques: interferometric; techniques: photometric; techniques: spectroscopic

Validation of Twelve Small Kepler Transiting Planets in the Habitable Zone - Caldwell, Douglas A.; Torres, Guillermo; Kipping, David M.; Ballard, Sarah; Batalha, Natalie; Borucki, William J.; Bryson, Steve; Ciardi, David R.; Crepp, Justin R.; Everett, Mark; Fressin, Francois; Henze, Christopher; et al. (2015)
We report on the work to validate twelve candidate-transiting planets from Kepler with orbital periods ranging from 34 to 207 days initially identified in the pipeline search of three years of Kepler data from quarters 1 to 12. The candidates were selected based on pipeline Data Validation models indicating that they are small and potentially in the habitable zone (HZ) of their parent stars. As their expected Doppler signals are too small for a direct measure of their masses, we verify their planetary nature by validating them statistically using the BLENDER technique. BLENDER simulates large numbers of false-positive scenarios and compares the resulting light curves with the Kepler photometry, taking into account additional information from the analysis of Kepler flux centroids and new follow-up observations, including high-resolution optical and NIR spectroscopy, adaptive optics imaging, and speckle imaging. For eleven of the candidates we show that the likelihood they are true planets is far greater than that of a false positive, to a 99.73% confidence level. For the twelfth candidate, the planet confidence level is about 99.2%. Using improved stellar parameters for the host stars, we derive planetary radii ranging from 1.12 to 2.73 R⊕. All twelve objects are confirmed to be in the HZ, and nine are small enough to be rocky. Excluding three of the candidates that have been previously validated by others, our study doubles the number of known potentially rocky planets in the HZ.
Conference Name: American Astronomical Society Meeting Abstracts #225 ADS Bibcode: 2015AAS...22543802C
Keywords: dept.phy

Validation of 12 small kepler transiting planets in the habitable zone - Torres, Guillermo; Kipping, David M; Fressin, Francois; Caldwell, Douglas A; Twicken, Joseph D; Ballard, Sarah; Batalha, Natalie M; Bryson, Stephen T; Ciardi, David R; Henze, Christopher E; Howell, Steve B; Isaacson, Howard; et al. (The Astrophysical Journal, 2015)
We present an investigation of 12 candidate transiting planets from Kepler with orbital periods ranging from 34 to 207 days, selected from initial indications that they are small and potentially in the habitable zone (HZ) of their parent stars. Few of these objects are known. The expected Doppler signals are too small to confirm them by demonstrating that their masses are in the planetary regime. Here we verify their planetary nature by validating them statistically using the BLENDER technique, which simulates large numbers of false positives and compares the resulting light curves with the Kepler photometry. This analysis was supplemented with new follow-up observations (high-resolution optical and near-infrared spectroscopy, adaptive optics imaging, and speckle interferometry), as well as an analysis of the flux centroids. For 11 of them (KOI-0571.05, 1422.04, 1422.05, 2529.02, 3255.01, 3284.01, 4005.01, 4087.01, 4622.01, 4742.01, and 4745.01) we show that the likelihood they are true planets is far greater than that of a false positive, to a confidence level of 99.73% (3σ) or higher. For KOI-4427.01 the confidence level is about 99.2% (2.6σ). With our accurate characterization of the GKM host stars, the derived planetary radii range from 1.1 to 2.7 R ⊕. All 12 objects are confirmed to be in the HZ, and nine are small enough to be rocky. Excluding three of them that have been previously validated by others, our study doubles the number of known rocky planets in the HZ. KOI-3284.01 (Kepler-438b) and KOI-4742.01 (Kepler-442b) are the planets most similar to the Earth discovered to date when considering their size and incident flux jointly. © 2015. The American Astronomical Society. All rights reserved..
94 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/036-512-292-095-617 tex.type: [object Object]
Keywords: dept.phy; methods: statistical; planetary systems; stars: individual (KOI-3284 (Kepler-438); KOI-4742 (Kepler-442)); techniques: photometric